ナンキョク ニ オケル ウチュウ ブッシツ ニ カンスル ケンキュウ IV ヤマト サンミャク インセキ ヒョウゲン ノ ヒョウガ コオリ ヨリ サイシュウ サレタ ウチュウジン - 矢吹, 貞代; ヤブキ, サダヨ; 矢内, 桂三; ヤナイ, ケイゾウ; 島, 誠; シマ, マコト; YABUKI, Sadayo; YANAI, Keizo; SHIMA, Makoto (国立極地研究所, 1976)
P(論文) 南極やまと山脈のいん石氷原より採取された氷河氷から,各種の宇宙塵を回収し,検討を行った.この研究の主目的は,異常な集積(濃集)を示すやまと隕石と宇宙塵との相互関係を調べることであった.しかし,予想に反して,特に宇宙塵の濃集は認められず,宇宙塵の降下量は,全地球に換算し年間(2.9-5.0)×10^4tであった.この値は昭和基地周辺の大陸氷(氷河氷)とほぼ同じである.この事実はやまと隕石が,シャワーとして落下した可能性の低いことを示唆しているといえよう.また,回収された宇宙塵は,その色と形態からa)黒色微球体,b)赤色,黄色,灰色ないし無色透明なガラス質微球体,c)不定形微球体に分けられる.a)の主成分はFe(60-65%)である.この試料は第15次日本南極地域観測隊(JARE1973-75)のやまと隕石探査隊により,1974年12月に裸氷の表面付近から採取されたものである. Black spherical microparticles, glassy microparticles and other irregular-shaped particles were collected from the glacier ice, sampled in December 1974, of the Meteorite Ice Field, Yamato Mountains. Their chemical and physical properties were compared with those of previously collected cosmic dust at various places in the world, and the relationship of these particles to the Yamato meteorites fall was also studied. Any specific particles associated with the Yamato meteorites were not confirmed. The annual accretion rate of black spherical microparticles on the whole earth is estimated at 2.9 to 5.0×l0^4t/year. This value agrees with the annual fall rate of cosmic dust collected from the Antarctic ice near Syowa Station. departmental bulletin paper